THE ROLE AND FUNCTION OF NOTARIES IN MAKING LEGISLATIVE ACTS BASED ON POSITIVE LAWS: THE REGULATORY OBSTACLE OF NOTARY - Rina Rina; Agus Yudha Hernoko; Rosnidar Sembiring; Hasim Purba (Green Publisher, 2024)
The profession of a notary has a very important meaning in social life. The notary is a powerful document maker in a legal process that carries out some of the public functions of the state, especially in the field of civil law the profession that performs legal services to the general public who have responsibility with respect to the means of authentic proof such as letters, documents or documents made in writing for various legal acts or other authority based on the wishes and requests of the parties. how the role and functions and the position of the notary in binding on the basis of positive legal glasses should be studied more thoroughly. The method of research is normative jurisprudence with the approach used in this research is the statue approach and the conceptual approach. (conceptual approach). In general, authentic acts relating to civil matters are made by the Notary and used as a means of proof by the parties. The authority of the notary/PPAT in the case of the creation of authentical acts against certain legal acts for the parties who want to do so does not give rise to a responsibility for the act that has been made by notary /PPAT because the role and functions of notaries are clearly only material, formal and material